A qualitative study to understand drivers of psychoactive substance use among Nepalese youth. - Tulsi Ram Bhandari (Public Library of Science (PLoS), 2021)
Background Psychoactive substance use among youth is an emerging public health issue in Nepal. This exploratory study aimed to better understand the drivers of psychoactive substance use among Nepalese youth in Rupandehi district of Nepal. Materials and methods This study used a qualitative approach for data collection. Both in-depth interviews (IDI, seven participants) and focus group discussions (FGD, 13 participants) were conducted among study participants who self-reported as psychoactive substance users or had history of psychoactive substance use. Participants for IDI were aged between 11 and 24 years and between 18 and 35 years old for FGDs. Semi-structured interview guides were prepared separately for IDIs and FDGs. Interviews were conducted in Nepali language and were audio recorded, which were there transcribed and translated into English for coding and analyses. In addition, interviews notes were taken by two research assistants. An inductive thematic analysis was used to analyze the data. Results This study identified a range of drivers of psychoactive substances use among Nepalese youths. Themes included (i) socio-cultural factors, (ii) individual factors, (iii) academic environment, (iv) physical environment and the (v) influence of media. The socio-cultural factors were categorized into sub-themes of family relationships, ethnic identity and psychoactive substance use and lack of social acceptance. Individual factors included peer pressure, stress relief and coping with financial challenges. Accessibility and availability of psychoactive substances in the surrounding environment and lack of monitoring and reinforcement of rules/ law and regulations were other drivers to psychoactive substance use among this Nepalese youth cohort. Conclusion Our study identified several important drivers of psychoactive substance use among youth in the Rupandehi district of Nepal. Future works are anticipated to further explore youth initiation and use of psychoactive substances and support the design of interventions that address these risk factors to reduce and prevent subsequent harms.